DESIGN AND DEVELOPMENT OF GASTRORETENTIVE DRUG DELIVERY SYSTEM OF CIPROFLOXACIN HYDROCHLORIDE - R, Vibin Bose (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim is to prepare the floating tablet of ciprofloxacin and to improve their bioavailability in the treatment against the Gram-positive and Gram-negative microorganisms. Ciprofloxacin HCL is an acidic drug used for respiratory tract infection, diarrhea, skin infection, thyroid fever, and urinary tract infection. The ciprofloxacin HCL is primarily absorbed in the stomach and it has low bioavailability. Due to its low availability, it was chosen as an appropriate drug for the scheme of the gastroretentive floating drug delivery system. Method: Ciprofloxacin HCl is an acidic drug which was made by wet granulation process using various polymers, which include hydroxypropyl methylcellulose K4M, Eudragit, and Guar gum with a different composition. The gas generating agents such as saleratus and citric acid were used for the preparation. The prepared granules were subjected to pre-compression parameters technique and the formulated tablets were subjected to post-compression parameters, respectively. Result: The Fourier-transform infrared analysis reveal that the drug and excipients used for the formulations were compatible with each other. All formulated granules having good flow properties and all the post-compression parameter are within the limit in which the F4 formulation shows optimum drug release of about 98.7% at 12 h and which has the buoyancy lag time of about 134 s and floating time about 12.5 h. Kinetic treatment revealed of the optimized preparation is based on Korsmeyer–Peppas model. The value n=0.861 states the process of non-Fickian diffusion. Conclusion: Based on above observation found in the work, it was concluded that ciprofloxacin HCl can formulate as a floating drug delivery system which helps in increasing the gastric residence time, as a result, it increases the bioavailability and half-life of ciprofloxacin HCl.